Comparative pharmacokinetic study of four major bioactive components after oral administration of Zhi‐Zi‐Hou‐Po decoction in normal and corticosterone‐induced depressive rats. (11th July 2019) - Bai, Yongtao; Song, Lihua; Zhang, Yongheng; Dai, Guoliang; Zhang, Weidong; Song, Shanshan; Sun, Hong; Jing, Wen; Xu, Meijuan; Ju, Wenzheng
Abstract: A highly selective and efficient LC–MS/MS method was developed to determine the plasma concentration of magnolol, hesperidin, neohesperidin and geniposide following oral administration of Zhi‐Zi‐Hou‐Po decoction in normal and depressed rats. Plasma samples were pretreated by protein precipitation with methanol. Chromatographic separation was performed on an XTerra ® MS C18 column using a gradient elution with a mobile phase composed of acetonitrile–0.1% aqueous formic acid. The proposed method was validated to be specific, accurate and precise for the analytes determination in plasma samples. The calibration curves displayed good linearity over definite concentration ranges for the analytes. The intra‐ and inter‐day precision of the proposed method at three different levels were all within <11.13% and the relative errors ranged from −8.46 to 8.93%. The recovery of the four compounds ranged from 82.72 to 89.08% and no apparent matrix effect was observed during sample analysis. After full validation, the established method was successfully applied for comparing the pharmacokinetics of four components between normal and depressed rats. The results showed that the AUC and C max of four analytes in depressed rats were significantly different from those in normal rats and might provide helpful information to guide the clinical use of Zhi‐Zi‐Hou‐Po to treat depression.